2007
DOI: 10.1053/j.jrn.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Mineral Bone Disorder and Health-Related Quality of Life Among Incident End-Stage Renal-Disease Patients

Abstract: Objective-To determine the extent to which chronic kidney disease mineral bone disorder (CKD-MBD) is associated with HRQOL among incident dialysis patients. Design-Cross-sectional analysis Setting-United States Renal Data System Dialysis Morbidity and Mortality Study (DMMS), Wave 2Patients-2590 adult participants in DMMS Wave 2 for whom quality of life and laboratory data were available Methods-We stratified patients according to their serum concentrations of phosphorus, calcium, and parathyroid hormone (PTH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…However, similar to our study, serum phosphorus level did not have any effect on MCS scores (13), and kidney disease symptoms. Nevertheless, another prior study demonstrated that high serum phosphorus levels management was associated with a considerable pill burden that was accompanying with lower quality of life in individuals with CKD (16).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, similar to our study, serum phosphorus level did not have any effect on MCS scores (13), and kidney disease symptoms. Nevertheless, another prior study demonstrated that high serum phosphorus levels management was associated with a considerable pill burden that was accompanying with lower quality of life in individuals with CKD (16).…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, admission in hospital would have been increased in association with hyperphosphatemia, high serum calcium level, and markedly increased serum PTH levels (13, 14, 25, 26) even in community-based sample of individuals without baseline CKD (26). On the other hand, another study found that the high mortality risk might be observed in low serum PTH levels (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor quality of life was evident before surgery, not directly related to the duration of the disease, as demonstrated 26,27 . However, the procedure had an important beneficial effect, which can be explained by the reduction of the toxic effects of PTH, causing multiple organ damage and exuberant symptomatology 28 .…”
Section: Discussionmentioning
confidence: 88%
“…They are responsible for disabling symptoms and consequences [1,2], impaired quality of life [3] and even increased mortality [4]. CKD-associated mineral and bone disorder has been identified as a potential risk factor for cardiovascular morbidity and mortality in this patient population [1,5]; hence, the term CKDmineral and bone disorder (CKD-MBD) has been suggested to describe the complexity of the syndrome [2].…”
Section: Introductionmentioning
confidence: 99%